THE CORRELATION BETWEEN STUDENTS’ WRITING MOTIVATION AND THEIR SKILL IN WRITING ENGLISH ARGUMENTATIVE TEXTS - Yolanda Putri Andeani; Widi Syaftinentias; Destri Wahyuningsih (J-Shelves of Indragiri (JSI), 2026)
This study aimed to examine the correlation between students’ writing motivation and their skill to writing English argumentative texts among eleventh-grade students at SMAN 2 Kelayang. A quantitative correlational research design was used, with 84 students participating in the study. The data were obtained through a writing motivation questionnaire and a writing test. Furthermore, the data were analyzed using the Pearson Product Moment Correlation test with SPSS version 27.The findings showed that the correlation coefficient between students’ writing motivation and writing skill was 0.753, indicating a strong positive correlation between the two variables. Additionally, the significance value was 0.000, which was lower than 0.05, indicating that the correlation was statistically significant.In conclusion, a significant positive correlation was found between students’ writing motivation and their writing skill in English argumentative texts. The results suggest that higher levels of motivation are associated with better writing performance.